PENGARUH LATIHAN BEBAN TERHADAP SHOOTING KE GAWANG PADA EKSTRAKURIKULER SEPAK BOLA. - Wardhana, Muhammad Ericho Imam; Atiq, Ahmad; Triansyah, Andika (Universitas Tanjungpura, 2023)
From the past and until now, there have been many changes in the sport of football, both from technical and non-technical factors, so I, as someone who pays little attention, also want to carry out studies both in literature and in fact to prove where the things I need to look at are sports. Football itself is a sport that is very popular and is practiced by people from Sabang to Merauke in the afternoon or early in the morning in order to achieve human desires in carrying out measurable and continuous sports activities. Each research step must have the right meaning and purpose to get the best data when conducting research, in this case, where the researcher chooses the right approach. Based on the research data that has been obtained and the results of calculating the data, it can be concluded that there is an effect of weight training on the results of shooting soccer in MAN 1 Ketapang students. This can be proven based on the calculation results, where the ttest value is 4.28 ttable value (1.815), so that the alternative hypothesis (Ha) is accepted and the null hipothesis (Ho) is rejected. This means that the research hypothesis states that there is an effect of weight training on the results of shooting soccer on students of MAN 1 Ketapang.